Tantangan dan Peluang Pewarta Foto Di Era Media Baru - Tripa Ramadhan; Fitria Ayuningtyas; Munadhil Abdul Muqsith (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Developments in technology and the internet have had a major influence on the journalism industry, including journalistic photography by photo journalists. Technological developments are not only in photography technology but also in the medium of publication. The rapid digitalization and development of social media gave rise to the term